The Principles of Subsidiarity and Effectiveness: Two Pillars of an Effective Remedy for Excessive Length of Proceedings within the Meaning of Article 13 ECHR (Polish Yearbook of International Law, 2021)
The purpose of this article is to determine the relationship between the principles of subsidiarity and effectiveness and an effective remedy for the excessive length of proceedings within the legal order of the European Convention on Human Rights. The article assumes that these key principles of the ECHR’s legal order have an impact on such a remedy, both in the normative and practical dimensions. This assumption has helped explain many aspects of the Strasbourg case law regarding this remedy. Concerning the relationship of this remedy with the principle of subsidiarity, it raises issues such as: the “reinforcing” of Art. 6 § 1; the “close affinity” of Arts. 13 and 35 § 1; and the arguability test. In turn, through the prism of the principle of effectiveness, the reasonableness criterion and the requirement of diligence in the proceedings are presented, followed by the obligations of States to prevent lengthiness of proceedings and the obligations concerning adequate and sufficient redress for such an excessive length of proceedings. The analysis shows that an effective remedy with respect to the excessive length of proceedings is not a definitive normative item, as the Court consistently adds new elements to its complex structure, taking into account complaints regarding the law and practice of States Parties in the prevention of and compensation for proceedings of an excessive length.